Leopold Bloom and the Unveiling of the Abject in Joyce’s Ulysses - Mubarak, Dr. Sobia (Journal of Research in Humanities, 2023)
This paper studies Ulysses in the light of Julia Kristeva’s theory of abjection posited in her essay, Powers of Horror. My focus will be on Leopold Bloom as the protagonist who represents all the traits that can be termed as “abjection of the self,” according to Kristeva’s definition. Leopold Bloom has also been looked at as the embodiment of the image of “the wandering Jew,” an abject figure. The paper also examines the link between women depicted in the novel and the state of Ireland as a colonized, abject space, being plundered and used as a commodity. In Kristeva’s view, “all literature is probably a version of the apocalypse” that seems to be rooted “on the fragile border (borderline cases) where identities (subject/object) do not exist or only barely so—double, fuzzy, heterogeneous, animal, metamorphosed, altered, abject” (Powers 207). James Joyce’s Ulysses, from this perspective, can be aptly considered a literary text which depicts a nation in a state of abjection, subjugated and dominated by the British Imperialist forces, tracing at the same time, the journey of its protagonist, Leopold Bloom, through the streets of Dublin, back to Ithaca/home. Leopold Bloom, a man of multiple origins, and uncertain religious identity: Irish/British, Catholic/Jewish, man/woman, represents a hybrid personality, a man in search of his authentic self.